ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN RUJUKAN PERSALINAN DI RUMAH SAKIT DR. R. ISMOYO KOTA KENDARI - Rio Kristian; Juminten Saimin; Ramadhan Tosepu (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Labor is greatly influenced by the environment and where the birth takes place. The place of delivery is one of the factors that can affect the psychology of the mother giving birth. The choice of place to give birth and birth attendants that are not appropriate will have a direct impact on the health of the mother. There are at least two choices of places to give birth, namely at the mother's house or at a health care facility. This study aims to analyze the factors associated with delivery referrals at Dr. R. Ismoyo Kendari City. Quantitative research method, analytic observational cross sectional study with simple random sampling technique which was carried out in August - October 2022 involving 37 mothers giving birth. Data analysis consisted of univariate, bivariate and multivariate analysis. The results showed that there was a significant relationship between the role of the family and referrals for childbirth (p-value 0.039), there was a significant relationship between costs and referrals for childbirth (p-value 0.010), there was a significant relationship between knowledge and referrals for childbirth (p-value 0.002), there was a significant relationship health service workers to delivery referrals (p-value 0.001), there is a significant relationship between service access and delivery referrals (p-value 0.035). The conclusion of the study is that research referrals are related to the variables of family roles, costs, knowledge, services of health workers. The cost variable is the variable that has the most influence on labor referrals.